Pembelajaran Penjasorkes Di Sekolah Dasar: Manfaat Olahraga Untuk Kesehatan Tubuh - Karina Nur Safitri; Salma Irdhillah; Mila Deskia; Moch Fitran Naufaldy; Restu Rahayu; Nazwa Kusumawicitra; Selvi Triwanvi; Agus Mulyana (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Sport is physical activity which is very important for body health. Physical fitness is the body's ability to function effectively at work or other activities. The research method in this article is a literature review to find sports activities that can be beneficial improves the immune system, mental health, metabolic health, muscle strength and function cardiovascular, increasing endurance, lowering cholesterol, reducing stress, burning fat, increasing immunity, preventing illness, improving blood circulation, and maintaining healthy bones and joints. If the exercise you do is not appropriate, it will have a bad impact in the future. To prevent disorders and decline, especially muscle size and strength, you can done with regular strength training. Exercising regularly can improve a person's quality of life, make the body healthier and stronger, and reduce the risk of disease. Exercise also helps increase flexibility, muscle elasticity and blood circulation, as well as speeding up the body's metabolism. Thus, exercising regularly and structured can be an integral part of a balanced and healthy lifestyle.